Strategies for RNA Resonance Assignment by 13C/15N- and 1H-Detected Solid-State NMR Spectroscopy - Aguion, Philipp Innig; Marchanka, Alexander (Frontiers in Molecular Biosciences, 2021)
Magic angle spinning (MAS) solid-state NMR (ssNMR) is an established tool that can be applied to non-soluble or non-crystalline biomolecules of any size or complexity. ssNMR method advances rapidly due to technical improvements and the development of advanced isotope labeling schemes. While ssNMR has shown significant progress in structural studies of proteins, the number of RNA studies remains limited due to yet underdeveloped ssNMR methodology. Resonance assignment is the most critical and limiting step in the structure determination protocol that defines the feasibility of NMR studies. In this review we summarize recent progress in RNA resonance assignment methods and approaches for secondary structure determination by ssNMR. We critically discuss advantages and limitations of conventional 13C- and 15N-detected experiments as well as novel 1H detected methods, identify optimal regimes for RNA studies by ssNMR and provide our view on future ssNMR studies of RNA in large RNP complexes.